Factores astronómicos que condicionan el clima y su influencia en la fenología de las plantas – revisión bibliográfica. - Moposita Molina, Daniel Jhoel (2021)
Astronomical factors, meteorological variables and phenological phases of plants are jointly associated with each other. Since ancient times this association of sciences has been reflected that day by day allow to open new fields that help to strengthen the study of Agriculture. In Ecuador, research related to these three sciences is not present in the national bibliographic bases. this is why this titling work has as its main objective to carry out and contribute with a bibliographic review of the astronomical factors that condition the climate and influence the phenology of the plants in order to continue future research work. The methodology used in the research starts with the search for 150 articles, where the selection of information was based on the determination of the specific study topic, bibliographic management, database purification and systematization, resulting in 78 verified documents among journal articles, theses, books and reports. The bibliographic review obtained 11 astronomical factors possibly related to plant meteorology and phenology. Among the most important are radiometry, moon, eclipses, solar radiation, cosmic rays and Earth movement. In the meteorological variables, 10 variables were found, these were selected according to the literature found. In the phenological phases, 21 documents were found where information is found of the most common periods in most plants, these being 8 phases. The documents are divided into 4 languages (English, Spanish, Portuguese and Russian), have 27 countries around the world and are reflected by the impact of each published journal with the exception of theses, books and reports. This information obtained is coded to generate possible study hypotheses for future research relating Astronomy, Meteorology and Agronomy.